OPTIMALISASI PERAN LEMBAGA PEMBERDAYAAN MASYARAKAT DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DI DESA AJAOBAKI KABUPATEN TIMOR TENGAH SELATAN - Akhmad Syafruddin; Junus Ekha Nahas Chornelis Nahas (CV. Adiba Aisha Amira, 2023)
Based on the suboptimal role of community empowerment institutions in supporting development in Ajaobaki Village, Mollo Utara Subdistrict, South Central Timor Regency, and the resulting impact on suboptimal development, this study uses a domestic regulation number 5 of 2007 on guidelines for organizing community institutions and the behavioralism approach, as well as Robert Chambers' theory of empowerment to analyze the role of community empowerment institutions in the economic empowerment of Ajaobaki Village. This study adopts a qualitative method and focuses on four main indicators of the role of community empowerment institutions in Ajaobaki Village. The research findings indicate that the Ajaobaki Village Empowerment Institution (LPM) as a facilitator has been optimal, as evidenced by the implementation of several community empowerment programs. However, as a mediator, the LPM's role is considered suboptimal due to traditional and ineffective processes of development information socialization. Additionally, the role of a mediator is not fully realized. The LPM's role as a motivator is also deemed suboptimal, as no active programs are in place. As a dynamic, the LPM's role is not optimal, with the explanation that the Ajaobaki Village LPM lacks performance in energizing empowerment programs. The inhibiting factors identified are institutional factors, namely the LPM itself, due to the inactivity of its members and the lack of specific work programs.